2017
DOI: 10.1111/cla.12196
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of Galerucinae (Coleoptera: Chrysomelidae) and the performance of mitochondrial genomes in phylogenetic inference compared to nuclearrRNAgenes

Abstract: With efficient sequencing techniques, full mitochondrial genomes are rapidly replacing other widely used markers, such as the nuclear rRNA genes, for phylogenetic analysis but their power to resolve deep levels of the tree remains controversial. We studied phylogenetic relationships of leaf beetles (Chrysomelidae) in the tribes Galerucini and Alticini (root worms and flea beetles) based on full mitochondrial genomes (103 newly sequenced), and compared their performance to the widely sequenced nuclear rRNA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 64 publications
12
87
0
Order By: Relevance
“…The DNA from all 46 samples was pooled in approximately equal concentrations and four Illumina TruSeq libraries were prepared with an average insert size of 450 bp (following Gillett et al, 2014;Nie et al, 2017). Each library was sequenced using the Illumina Hiseq2500 platform at BerryGenomics (China) with 250-bp paired-end reads setting.…”
Section: Mitochondrial Genome Sequencing and Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA from all 46 samples was pooled in approximately equal concentrations and four Illumina TruSeq libraries were prepared with an average insert size of 450 bp (following Gillett et al, 2014;Nie et al, 2017). Each library was sequenced using the Illumina Hiseq2500 platform at BerryGenomics (China) with 250-bp paired-end reads setting.…”
Section: Mitochondrial Genome Sequencing and Assemblymentioning
confidence: 99%
“…The site-heterogeneous CAT model implemented in phylobayes is a Dirichlet process mixture of profiles of equilibrium frequencies combined with general exchange rates (Lartillot et al, 2009). Recent studies have shown CAT-based models reduce the susceptibility of analyses to long-branch attraction, resulting in more robust topologies (Lartillot et al, 2009;Li et al, 2015Li et al, , 2017Timmermans et al, 2015;Feuda et al, 2017;Nie et al, 2017;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(see e.g., Wilcox 1975; Medvedev 2012; Lee et al 2016). However, its position is still questionable (Nie et al 2017). …”
Section: Resultsmentioning
confidence: 99%
“…1). Among these tree hypotheses, a sister group relationship of Galerucinae and Alticinae was supported by the most molecular or morphological analyses (Seeno and Wilcox 1982; Doguet 1994; Farrell 1998; Gómez-Zurita et al 2007; Hunt et al 2007; Bouchard et al 2011; Ge et al 2011, 2012; Nie et al 2017). Some of the recently established groupings, based on DNA sequences, still need further in-depth analysis because they are phylogenetically and biogeographically incomplete (Biondi and D´Alessandro 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation